Perception and analysis of Chinese accented German vowels - DING, Hongwei; JOKISCH, Oliver; HOFFMANN, Rüdiger (Archives of Acoustics, 2007)
This report describes an investigation to obtain specific knowledge about the production of German vowels by Chinese speakers. The experiments have been conducted to acquire both perceptual and acoustic measures of the vowels. 11 Chinese speakers have been selected as subjects to read 20 German words. The assessment was conducted by 10 German native speakers. We came to the conclusion that the Chinese speakers have little difficulty in pronouncing long vowels. However, they are not accurate in the short vowels production. In the further acoustic investigation, it was discovered that the Chinese speakers are not always aware of the duration contrast of long-short vowels, and they have some difficulty in finding the right position of the tongue and to grasp the degree of lip-rounding in central vowels production. Those deviations can contribute to the foreign accent of the Chinese German speakers.